Effectiveness of Intervention Strategies to Increase Adolescents' Physical Activity and Reduce Sedentary Time in Secondary School Settings, Including Factors Related to Implementation: A Systematic Review and Meta-Analysis - Ana María Contardo Ayala; Kate Parker; Emiliano Mazzoli; Natalie Lander; Nicola D. Ridgers; Anna Timperio; David R. Lubans; Gavin Abbott; Harriet Koorts; Jo Salmon (SpringerOpen, 2024)
Abstract Background Globally, just one in five adolescents meet physical activity guidelines and three-quarters of the school day is spent sitting. It is unclear which types of school-based interventions strategies increase physical activity and reduce sedentary time among adolescents, or how these interventions are implemented influences their effectiveness. Objective The three aims of our systematic review were to (a) identify intervention strategies used within secondary school settings to improve students' movement behaviours throughout school-based initiatives, delivered at or by the school; (b) determine the overall effect of the interventions (meta-analysis) on physical activity (all intensities), sedentary time, cognitive/academic, physical health and/or psychological outcomes; and (c) describe factors related to intervention implementation. Methods Searches were conducted in MEDLINE complete, EMBASE, CINAHL, SPORTDiscus, APA PsycINFO, and ERIC in January 2023 for studies that (a) included high school-aged adolescents; (b) involved a school-based intervention to increase physical activity and/or decrease sedentary time; and (c) were published in English. Reported effects were pooled in meta-analyses where sufficient data were obtained. Results Eighty-five articles, representing 61 interventions, met the inclusion criteria, with 23 unique intervention strategies used. Interventions that involved whole-school approaches (i.e., physical activity sessions, environmental modifications, teacher training, peer support and/or educational resources) were favourably associated with most of the outcomes. The meta-analyses showed: (a) non-significant effects for sedentary time (Standardized mean difference [SMD] = -0.02; 95%CI, -0.14, 0.11), physical activity at all intensities (light: SMD= -0.01; 95%CI, -0.08, 0.05; moderate: SMD = 0.06; 95%CI, -0.09, 0.22; vigorous: SMD = 0.08; 95%CI, -0.02, 0.18; moderate-to-vigorous: SMD = 0.05; 95%CI, -0.01, 0.12) and waist circumference (SMD = 0.09; 95%CI, -0.03, 0.21), and (b) a small statistically significant decrease in body mass index (SMD= -0.09, 95%CI -0.16, -0.0). Factors related to intervention implementation were reported in 51% of the articles. Conclusion While some intervention approaches demonstrated promise, small or null effects were found in meta-analyses. Future school-based interventions should utilize a whole-school approach designed to increase adolescents' activity across the day. Consistent reporting of implementation will increase understanding of how interventions are adopted, implemented and sustained. Registration PROSPERO (CRD42020169988).